Experiences and perceptions among intensive care nurse in caring patient with delirium / Azizah Ahmad Aduan - Ahmad Aduan, Azizah (2019)
Delirium event in ICU has strong associates’ outcome in increasing the length of the stay in ICU, length of time in ventilators, increase mortality in adults and developed post ICU cognitive impaired. The occurrence of delirium could be prevented in ICU with the existing of delirium screening tools and sedation protocol which enable ICU nurses (ICN) and others clinician to recognize and prevent it. ICN is the key of this study. The aim of this study is to explore the experience and perception among ICN while taking care patient with delirium. This study utilized descriptive phenomenological qualitative. Eight ICN were participated in depth interview (IDI) using semi-structure interview in HTAA, Kuantan. Audio recordings of the transcripts, observation field, observation of document used were coded and analysed thematically. The findings are captured predominant themes “catalyst delirium in ICU”. The emergent themes derived inductively reflected clearly on experience and perception of ICN were titled as follows: 1) laborious work 2) marvel on delirium, sedation and agitation 3) influential factors 4) the impact of tools. The results of this qualitative study have provided a rich information of backbreaking work while handling delirium patients. ICN also found still lacking in delirium recognition due to absenteeism delirium education. Suggestion for forming specialization team for detect delirium and collaborate with other professionals’ healthcare provider to smooth delirium assessment and management. Delirium screening tools also not available in ICU, HTAA to helps ICN recognize delirium in ICU. Therefore, suggestion in this study to place delirium screening tools in ICU with comprehensive protocol, policy and guidelines for the user.